2016
DOI: 10.1016/j.jsha.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant activated factor VII for uncontrolled bleeding postcardiac surgery

Abstract: In this analysis, rFVIIa succefully reduced the chest tube bleeding and blood products transfused during severe post cardiac surgical bleeding. However, safety of rFVIIa remains unclear. Prospective controlled trials are still needed to confirm the role of rFVIIa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…We found no significant differences noted between the two groups of this study with respect to DDAVP usage or dose; approximately half of the patients in each group received DDAVP. Recombinant activated factor VII has been used in the setting of acute hemorrhage as well as uncontrolled bleeding postcardiac surgery 22‐24 . The utilization of activated factor VII for the treatment of bleeding in patients without haemophilia was reviewed in a Cochrane Systematic Review and found a significant increase in the risk for thromboembolic embolic complications as well mixed evidence to support the use of activated factor VII as a general hemostatic agent 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no significant differences noted between the two groups of this study with respect to DDAVP usage or dose; approximately half of the patients in each group received DDAVP. Recombinant activated factor VII has been used in the setting of acute hemorrhage as well as uncontrolled bleeding postcardiac surgery 22‐24 . The utilization of activated factor VII for the treatment of bleeding in patients without haemophilia was reviewed in a Cochrane Systematic Review and found a significant increase in the risk for thromboembolic embolic complications as well mixed evidence to support the use of activated factor VII as a general hemostatic agent 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant activated factor VII has been used in the setting of acute hemorrhage as well as uncontrolled bleeding postcardiac surgery. [22][23][24] The utilization of activated factor VII for the treatment of bleeding in patients without haemophilia was reviewed in a Cochrane Systematic Review and found a significant increase in the risk for thromboembolic embolic complications as well mixed evidence to support the use of activated factor VII as a general hemostatic agent. 25 In our study, activated factor VII was only given to four patients, all in the no 4PCC group, before the US market release of 4PCC.…”
Section: Discussionmentioning
confidence: 99%
“…2 The use of concentrated coagulation factor replacement following CPB to control persistent bleeding after heparin reversal has become more commonplace. Studies of activated recombinant factor VII (rFVIIa) use [5][6][7][8][9][10][11] have found that rFVIIa is effective at reducing chest tube output and blood product transfusion requirements. [6][7][8][9] A recent study by Downey et al looked at rFVIIa in pediatric cardiac patients and found that perioperative administration of rFVIIa was associated with an increased incidence of postoperative thrombotic complications when compared with match controls.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of activated recombinant factor VII (rFVIIa) use [5][6][7][8][9][10][11] have found that rFVIIa is effective at reducing chest tube output and blood product transfusion requirements. [6][7][8][9] A recent study by Downey et al looked at rFVIIa in pediatric cardiac patients and found that perioperative administration of rFVIIa was associated with an increased incidence of postoperative thrombotic complications when compared with match controls. 12 Studies evaluating prothrombin complex concentrate (PCC) found that use of PCC was associated with significantly decreased 24-h postoperative blood loss when compared with fresh frozen plasma [13][14][15] without increasing the risk of thromboembolic complications or mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant activated factor VII (rFVIIa) was developed in the 1970s and used clinically in the 1980s for patients with haemophilia at doses of 90 mg/kg [1]. Off-label use of rFVIIa for perioperative cardiac surgical bleeding has been shown to reduce bleeding [2][3][4][5], blood product administration [4,6,7] and the rate of reoperations [2,8]. However, the use of rFVIIa for cardiac surgical bleeding has also been associated with increased mortality [9], thrombosis [10][11][12], stroke [8,12,13] and renal morbidity [9,10].…”
Section: Introductionmentioning
confidence: 99%